Free radical properties of metal complexes - Szentmihályi, Klára; Blázovics, Anna; Vinkler, Péter (Acta Biologica Szegediensis, 2003)
Since metals are cable of catalysing the free radical reactions, different metal (Mg, Mn, Zn) compounds were studied to determine their hydroxyl radical generating and/or scavenging abilities depending on ligand in a H2O2/•OH -luminol system with or without microperoxidase. Magnesium oxide, magnesium gluconate and manganese gluconate increase the free radical reactions in the H2O2/•OH -luminol system. Most of examined metal compounds have different hydroxyl radical scavenging activity in H2O2/•OH- microperoxidase -luminol system. Magnesium citrate has the highest antioxidant effect, while manganese compounds seem to be prooxidant. Vitamin E and C elevate the free radical level in this experimental system.